Clinical and laboratory features of ixodes tick-born borreliosis caused by Borrelia miyamotoi in children - N. V. Skripchenko; A. A. Balinova (Журнал инфектологии, 2014)
The article presents the results of a survey of 77 patients with confirmed acute tick-borne infection in the age of 1 year to 17 years. Three patients (5%) selected Borrelia miyamotoi. Identified clinical and laboratory features of infection caused by Borrelia miyamotoi. It is shown that Borrelia miyamotoi causes the development of recurrent febrile conditions without erythema migrans at the background of marked cerebral symptoms. In this regard, necessary to carry out a differential diagnosis of this disease with tick borne encephalitis.